Avian influenza A virus H7N9 in China, a role reversal from reassortment receptor to the donator. Issue 1 (21st December 2022) - He, Jun; Hou, Sai; Xiong, Chenglong; Hu, Linjie; Gong, Lei; Yu, Junling; Zhou, Xiaoyu; Chen, Qingqing; Yuan, Yuan; He, Lan; Zhu, Meng; Li, Weiwei; et al.
Abstract: Reassortment can introduce one or more gene segments of influenza A viruses (IAVs) into another, resulting in novel subtypes. Since 2013, a new outbreak of human highly pathogenic avian influenza has emerged in the Yangtze River Delta (YRD) and South‐Central regions of China. In this study, using Anhui province as an example, we discuss the possible impact of H7N9 IAVs on future influenza epidemics through a series of gene reassortment events. Sixty‐one human H7N9 isolates were obtained from five outbreaks in Anhui province from 2013 to 2019. Bioinformatics analyses revealed that all of them were characterized by low pathogenicity and high human or mammalian tropism and had introduced novel avian influenza A virus (AIV) subtypes such as H7N2, H7N6, H9N9, H5N6, H6N6, and H10N6 through gene reassortment. In reassortment events, Anhui isolates may donate one or more segments of HA, NA, and the six internal protein‐coding genes for the novel subtype AIVs. Our study revealed that H7N9, H9N2, and H5N1 can serve as stable and persistent gene pools for AIVs in the YRD and South‐Central regions of China. Novel AIV subtypes might be generated continuously by reassortment. These AIVs may have obtained human‐type receptor‐binding abilities from their donors and prefer binding to them, which can cause human epidemics through accidental spillover infections. Facing the continual threat of emerging avian influenza, constant monitoring of AIVs should be conducted closely for agricultural and public health.